REVITALISASI KAWASAN MASJID KERAMAT BANUA HALAT - Aritonang, Sofyan Rachman; Heldiansyah, JC (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2022)
The area Banua Halat Sacred Mosque in Tapin Regency, which has degraded its environment due to inadequate facilities and infrastructure services, and does not have a forum for development and introduction to religious and cultural history, it is feared that cultural heritage will be damaged, couple with the case of the COVID-19 pandemic which hampers activities. Baayun Maulid Nabi Muhammad, which is held every 12 rabiul awal every year, reduces the existence of areas. With the development of cultural heritage that elevates historical and cultural values, it will have an impact on the environment and the surrounding community. The revitalization of the mosque area is carried out with the aim of rediscovering the potential that has or was owned or should have been owned by the sacred Banua Halat mosque. Trough the method of forming the area through the concept of God to express directly the relationship between religion and culture produces clarity of form and space, shape, and order by increasing the vitality of the area through service network facilities and infrastructure, as well as developing the value of the location of the cultural heritage area. Keywords: Banua Halat Sacred Mosque, Cultural Conservation, Devine Rantau, Revitalization.